Study of Education Analysis of Alpha Generation in Marginal Communities - Hidayat, Taupik; Matondang, Arnan Pahmi; Syukron, Ahmad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The phenomenon of the world of education that exists today is the importance of education for the future generation is increasingly recognized by all people, including the alpha generation from marginalized communities, but the classic problem has not been resolved. School fees are still difficult for them to afford, even though the government has provided free primary to secondary education, in practice, the lower classes still have to have additional income in order to meet the educational needs of their sons and daughters. The conclusion of this study is that it is still difficult for the alpha generation of marginalized communities to obtain access to decent education, this is due to several factors, such as economic factors, facilities, learning opportunities and access to technology and information. In the existing limitations, it turns out that not a few of the alpha generation of marginalized communities have succeeded in achieving achievements and success in their education. This is able to provide encouragement for other children who are in the same economic conditions, they believe that opportunities can be created as long as the spirit to learn remains without giving up.